Morphological influence of cellulose nanoparticles (CNs) from cottonseed hulls on rheological properties of polyvinyl alcohol/CN suspensions. (20th November 2016) - Zhou, Ling; He, Hui; Li, Mei-Chun; Song, Kunlin; Cheng, H.N.; Wu, Qinglin
Highlights: Cottonseed hulls were evaluated for cellulose nanomaterials extraction. The rheological behavior of CN suspensions was strongly dependent on CN morphology. The recommended weight ratio of CNFs to PVA were less than 3% in 5% PVA solution. For SCNCs, the optimized weight ratio were less than 6% in 5% PVA solution. CNCs could be used at weight ratio up to 9% of PVA in the 15 wt% PVA solution. Abstract: The present work describes the isolation of cellulose nanoparticles (CNs) with different morphologies and their influence on rheological properties of CN and CN-poly (vinyl alcohol) (PVA) suspensions. Cottonseed hulls were used for the first time to extract three types of CNs, including fibrous cellulose nanofibers, rod-like cellulose nanocrystals and spherical cellulose nanoparticles through mechanical and chemical methods. Rheology results showed that the rheological behavior of the CN suspensions was strongly dependent on CN concentration and particle morphology. For PVA/CN systems, concentration of PVA/CN suspension, morphology of CNs, and weight ratio of CN to PVA were three main factors that influenced their rheology behaviors. This research reveals the importance of CN morphology and composition concentration on the rheological properties of PVA/CN, providing new insight in preparing high performance hydrogels, fibers and films base on PVA/CN suspension systems.